Book Reviews. Issue 2 (1st December 2019) - Ferns, Nicholas; Farley, David; Beeton, Sue; Mota Santos, Paula; Luchmun, Rachel
Abstract : Carla Manfredi. Robert Louis Stevenson's Pacific Impressions: Photography and Travel Writing, 1888–1894 (Palgrave Macmillan, 2018), 256 pp., ISBN: 978-3-319-98312-7, €69.99 (hardcover). Richard Ivan Jobs. Backpack Ambassadors: How Youth Travel Integrated Europe (Chicago: University of Chicago Press, 2017) 360pp, ISBN-13: 978-0-226-46203-5, $35.00 (paper). Youngmin Choe. Tourist Distractions: Travelling and Feeling in Transnational Hallyu Cinema (Durham and London: Duke University Press, 2016), xii + 252pp., ISBN-978-0-8223-6130-5, $60.99 (pbk). Valerio Simoni. Tourism and Informal Encounters in Cuba (Oxford; Berghahn, 2016), 282+xvi pp, ISBN 978-1-78533-833-5, $27.95 (paperback). Sabine Marschall. Tourism and Memories of Home: Migrants, Displaced People, Exiles and Diasporic Communities (Bristol: Channel View Publications, 2017), xv + 288 pp., ISBN 13: 978-1-84541-602-7, $49.95 (paperback).